Enhancement of waste activated sludge (WAS) anaerobic digestion by means of pre- and intermediate treatments. Technical and economic analysis at a full-scale WWTP. (15th June 2018) - Campo, Giuseppe; Cerutti, Alberto; Zanetti, Mariachiara; Scibilia, Gerardo; Lorenzi, Eugenio; Ruffino, Barbara
Abstract: Anaerobic digestion (AD) is the most commonly applied end-treatment for the excess of waste activated sludge (WAS) generated in biological wastewater treatment processes. The efficacy of different typologies of pre-treatments in liberating intra-cellular organic substances and make them more usable for AD was demonstrated in several studies. However, the production of new extracellular polymeric substances (EPSs) that occur during an AD process, due to microbial metabolism, self-protective reactions and cell lysis, partially neutralizes the benefit of pre-treatments. The efficacy of post- and inter-stage treatments is currently under consideration to overcome the problems due to this unavoidable byproduct. This work compares three scenarios in which low-temperature (<100 °C) thermal and hybrid (thermal+alkali) lysis treatments were applied to one sample of WAS and two samples of digestate with hydraulic retention times (HRTs) of 7 and 15 days. Batch mesophilic digestibility tests demonstrated that intermediate treatments were effective in making the residual organic substance of a 7-day digestate usable for a second-stage AD process. In fact, under this scenario, the methane generated in a two-stage AD process, with an in-between intermediate treatment, was 23% and 16% higher than that generated in the scenario that considers traditional pre-treatments carried out with 4% NaOH at 70 and 90 °C respectively. Conversely, in no cases (70 or 90 °C) the combination of a 15-day AD process, followed by an intermediate treatment and a second-stage AD process, made possible to obtain specific methane productions (SMPs) higher than those obtained with pre-treatments. The results of the digestibility tests were used for a tecno-economic assessment of pre- and intermediate lysis treatments in a full scale wastewater treatment plant (WWTP, 2, 000, 000 p.e.). It was demonstrated that the introduction of thermal or hybrid pre-treatments could increase the revenues from the electricity sale by between 13% and 25%, in comparison with the present scenario (no lysis treatments). Conversely, intermediate treatments on a 7-day digestate could provide a gain of 26% or 32%, depending on the process temperature (70 or 90 °C). Highlights: EPS limits the efficacy of pre-treatments in the WAS digestion. Efficacy of pre- and intermediate treatments on WAS was tested at a lab scale. A 2-stage process on a 7-d digestate produced 20% more methane than pre-treatment. In no cases a treated 15-d digestate was more productive than a pre-treated WAS. Gains of 30% from electricity sale were obtained with a 2-stage process on a 7-d digestate.